An Archaeology of Passage: Adrian Piper Passing and Not Passing as the Mythic Being - Cat Dawson (Sillages Critiques)
One of the most referenced in the oeuvre of the conceptual artist Adrian Piper is an early series called The Mythic Being (1973-1975), based on a series of photographs of the artist in drag. Mythic Being is also, however, one of the most contested projects in the artist’s oeuvre. Building off of the ambiguous racial and gender markers in the piece, scholars who have worked on the piece have made a range of argument staked not only on fixing the race or gender of the figure, but also conditioning the fixing of one marker or the other. In contrast to that discursive disciplining, this paper argues that the Mythic Being is a fungible figure whose identifications are radically contingent and ultimately undecidable. Through a close reading of several frequently cited but infrequently closely read objects from the series, I suggest that we need not foreclose on the myriad forms of passing within the project to find the politics within. I also call up Piper’s oft-elided indebtedness to Black and feminist representational strategies to both demonstrate the centrality of those traditions to postmodernism, and to reveal a new perspective on the work as participating in a coalition politics via social address.